EKSTERNALISASI GAYA PAKAIAN THE NURULS GENERASI Z DALAM BERPAKAIAN ISLAMI DI KABUPATEN BOGOR - Sarah, Nayla; Ernawati, Erna; Surizkika, Aldi (JURNAL SAHID DA'WATII, 2025)
The majority of various groups, including generation Z, choose a simple style of clothing as their daily clothing style with a percentage of 73%. On the other hand, Islamic clothing is often juxtaposed with the idea of ​​"fast fashion" which aims to combine modesty with a fashionable style. very popular with generation Z. The externalization of The Nuruls' clothing style in this case can be seen in their efforts to balance the diversity of global fashion trends with religious obligations. The aim of this research is to determine the process of externalizing Nurul's fashion style in generation Z in Islamic clothing. This research method uses qualitative methods. The results suggest that Generation Z's externalization process involves observing, adopting, and expressing external inspiration into the individual's personal style identity. In conclusion, there are significant changes in the clothing style of generation Z in Bogor Regency.